PENGARUH BUDAYA KERJA, KOMITMEN KARYAWAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA CV ULTRA OUTBOND ADVENTURE - Munthe, Alexander Chrisse Ginting; Sitompul, Pandapotan (UNIKA Santo Thomas, 2025)
This study aims to analyze the influence of work culture, employee commitment, and motivation on employee performance at CV. Ultra Outbond Adventure, a company engaged in the field of education services, outbound training, and human resource development. The research employs a quantitative approach with data collected through questionnaires distributed to a total population of 73 operational employees using a saturated sampling technique. The research variables include work culture, employee commitment, and motivation as independent variables, while employee performance serves as the dependent variable. Data analysis was conducted using multiple linear regression, complemented by t-test, F-test, and coefficient of determination (R²). The results indicate that both partially and simultaneously, work culture, employee commitment, and motivation have a positive and significant effect on employee performance. Specifically, improvements in work culture, commitment, and motivation are proven to enhance employee performance levels significantly. The R Square value of 0.635 indicates that 63.5% of the variation in employee performance can be explained by these three variables, while the remaining 36.5% is influenced by other factors not examined in this study. These findings highlight the importance of strengthening organizational culture, fostering employee commitment, and enhancing motivation as strategic efforts to improve overall performance and organizational competitiveness in the service industry.